A Comparison of the Descriptive Information from the MMPI–2 and MMPI–2–RF. Issue 1 (2nd January 2020) - Dodd, Cody G.; Courrégé, Seth C.; Weed, Nathan C.; Deskovitz, Mark A.
Abstract: Do MMPI–2 or MMPI–2–RF profiles differ in how accurately they depict examinees? To explore this question, we examined differences in clinical descriptions of equivalent profiles from the two instruments. Fourteen valid MMPI–2 protocols from an archival private practice sample were scored as both the MMPI–2 and the MMPI–2–RF. The resulting 28 profiles were coded separately by four raters using the Midwestern Q-Sort. Examinee descriptions from the two instruments were compared in terms of their (a) similarity, operationalized by q-correlations between corresponding MMPI–2 and MMPI–2–RF ratings; (b) descriptive validity, operationalized by correlations with q-sorts provided by the examinees' therapists; and (c) incremental descriptive validity, operationalized by incremental prediction of the therapist q-sorts by the MMPI–2 and MMPI–2–RF, one over the other. Descriptions from corresponding MMPI–2 and MMPI–2–RF score reports were highly intercorrelated. Ratings from both were valid predictors of therapist descriptions, and neither clearly outperformed the other in terms of incremental validity.